The challenges of Sustainable Development (SD) – Case of Morocco - MCHICH, Hamza; EL KADIRI, Kenza (Revue Internationale du Chercheur, 2021)
The term "sustainable development" refers to a common philosophy that promotes the balance of human interests, economic development, environmental sustainability and the preservation of social and societal balances. Surprisingly, the path we could take, as well as what has been reflected in various media, would not limit long-term growth to the environmental cliff. Much has been written about sustainable development. Many social actors, institutions and organizations are calling for it. The environment is a public good that everyone enjoys without necessarily paying the price. This “free” approach has resulted in waste of natural resources and climate change that challenges our sustainable development opportunities. The objective of this article is to highlight the various challenges and concerns that hinder Morocco’s long- term development. This study reflects on the foundations and specificities of sustainable growth as a general solution to maintain the long-term viability of our environments, habitats and economies.